2017
DOI: 10.7717/peerj.3337
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of postoperative hypokalemia in pituitary adenomas after transsphenoidal surgery

Abstract: BackgroundPituitary adenoma is one of the most common intracranial neoplasms, and its primary treatment is endoscopic endonasal transsphenoidal tumorectomy. Postoperative hypokalemia in these patients is a common complication, and is associated with morbidity and mortality. This study aimed to analyze the etiopathology of postoperative hypokalemia in pituitary adenomas after endoscopic transsphenoidal surgery.Methods and MaterialsThis retrospective study included 181 pituitary adenomas confirmed by histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In contrast to conventional craniotomy surgery, transsphenoidal surgery is distinguished by reduced tissue damage, decreased operative duration, and expedited postoperative recuperation. While transsphenoidal surgery is considered a safer alternative, electrolyte imbalances, particularly hyponatremia and hypokalemia, are frequently encountered [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to conventional craniotomy surgery, transsphenoidal surgery is distinguished by reduced tissue damage, decreased operative duration, and expedited postoperative recuperation. While transsphenoidal surgery is considered a safer alternative, electrolyte imbalances, particularly hyponatremia and hypokalemia, are frequently encountered [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the use of glucocorticoids and mineralocorticoids during the operation can cause a decrease in blood potassium levels. Secondly, destruction of pituitary cells during surgery can release hormones, and the tumor tissue is squeezed out, leading to further hormone secretion [20]. The most common cause of delayed hyponatremia is syndrome of inappropriate antidiuretic hormone secretion (SIADH) [5], and early release of ADH may also cause hypokalaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent evidence has demonstrated that this association was possibly due to age-related differences in body mass composition, which results in physiologically low total exchangeable body potassium in older patients (Kleinfeld et al, 1993). Many researchers have also concluded that the type of PA is associated with a difference in the prevalence of hypokalemia (Fan et al, 2020;You et al, 2017). You et al (2017) reported that, compared with other specific types of PA, patients with ACTH-PAs had a significantly higher prevalence of postoperative hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have also concluded that the type of PA is associated with a difference in the prevalence of hypokalemia (Fan et al, 2020;You et al, 2017). You et al (2017) reported that, compared with other specific types of PA, patients with ACTH-PAs had a significantly higher prevalence of postoperative hypokalemia. ACTH-secreting PAs are related to a clinical disorder known as Cushing's disease (CD), and hypokalemia is a common feature in patients with CD.…”
Section: Discussionmentioning
confidence: 99%